Cultural adaptation of the Glamorgan Scale to Brazilian Portuguese: Pressure Injury in Pediatrics - Vocci, Marcelli Cristine [UNESP]; Bertoncello Fontes, Cassiana Mendes [UNESP]; Fernandes Abbade, Luciana Patricia [UNESP] (Univ Sao Paulo, Escola De Enfermagem De Ribeirao Preto, 2021)
Objective: to describe the methodological process of cultural adaptation of the Glamorgan Scale to Brazilian Portuguese. Method: a methodological study of translation and cultural adaptation of the Glamorgan Scale, following the six stages: initial translation, synthesis of translations, back-translation, committee of experts, pre-test, and submission of the adapted version to the author for approval. The committee of experts was composed of five physicians and, during evaluation, a semantic, idiomatic, cultural and conceptual analysis was carried out. The agreement and representativeness of the items were assessed using the Content Validity Index. A minimum value of 80% agreement was considered. Results: all stages of the translation and cross-cultural adaptation process were satisfactory. In the evaluation made by the committee of experts, all items obtained an agreement greater than 80% in the first evaluation round. The pre-test stage allowed for a critical overview of the instrument, where few modifications were suggested by the participants. Conclusion: the Glamorgan Scale was translated and culturally adapted to Brazilian Portuguese. Future psychometric studies are necessary to validate the scale.
Keywords: Translating; Transcultural Studies; Nursing Methodology Research; Pressure Ulcer; Quality of Health Care; Pediatric Nursing